2021
DOI: 10.1088/1755-1315/752/1/012011
|View full text |Cite
|
Sign up to set email alerts
|

Insect Population in Rice Ecosystems with Various Types of Irrigation and Local Rice Varieties

Abstract: System of Rice Intensification is a new method of cultivation that has been widely done to improve the efficiency of water use, which can affect pest and predator populations. The research aims to determine the types of pests and natural enemies as predators in various irrigations and local varieties of rice. The study was conducted at the Research Field and Laboratory of Protection of the Faculty of Agriculture, University of Muhammadiyah Yogyakarta. The research was carried out with a 3x4 Strip Plot Design i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Comparatively, these findings are in line with the outcomes of Asghar et al [15], who observed differential species compositions between varying agricultural management practices. The study by Isnawan and Ramadhanti [28] further corroborates these results by reporting a similar pattern of insect species distribution within Nigerian rice ecosystems.…”
Section: Discussionsupporting
confidence: 70%
“…Comparatively, these findings are in line with the outcomes of Asghar et al [15], who observed differential species compositions between varying agricultural management practices. The study by Isnawan and Ramadhanti [28] further corroborates these results by reporting a similar pattern of insect species distribution within Nigerian rice ecosystems.…”
Section: Discussionsupporting
confidence: 70%
“…Pests found on rice plants consist of the order Diptera (Tephritidae), Hemiptera (Cicadellidae and Coreidae), Lepidoptera (Crambidae) [4], and Orthoptera (Acrididae, Gryllidae, and Pyrgomorphidae). Insect pests that attack rice plants are identified based on family abundance [5]. In addition, the insect S. litura Fabricius (Lepidoptera: Noctuidae) [6], or armyworm, is an important pest in rice plants [7].…”
mentioning
confidence: 99%
“…The biotic component that controls insect populations of pests in agroecosystems is a natural enemy. Natural enemies of rice wetland agroecosystems include predators, parasitoids, and entomopathogens [5].…”
mentioning
confidence: 99%